ASAS CONTRA LEGEM HAKIM SEBAGAI UPAYA PERLINDUNGAN HAK PEREMPUAN DALAM PEMBAGIAN HARTA BERSAMA PASCA PERCERAIAN - Fathiya Khaerunnisa (2023)
This study seeks to examine the application of the contra legem principle by judges in an effort to protect women's rights in the distribution of joint assets after divorce, as well as the legal settlement efforts if joint property decisions are not implemented and the implications of its application for the parties involved. The method used in this study is a normative juridical method, with a statutory approach and a case approach. This study demonstrates that the problem regarding the distribution of joint assets after a complicated divorce requires judges to be able to find laws that are in accordance with how to explore the values of justice that exist in society, even if this necessitates a judge deciding a case by disregarding the regulations written. In deciding how to divide community property, judges who apply contra legem assess the rights and responsibilities ex-husbands and wives exercised during their marriage. The aggrieved party has the right to submit a request for execution to the court if the decision is not implemented by one of the parties. If distribution is based on contributions and estimates of future requirements, the implications of applying this principle can provide legal protection benefits for the parties involved, particularly women.